f(x) = (x + 1)^2 and g(x) = 2(x - 1) Show that gf(x) = 2x(x + 2)

For this question, as we are looking for gf(x) so we first need to plug in our formula for f(x) into the g(x) formula, giving us:
2((x+1)^2 - 1)
We can then expand our squared bracket to get:
2(x^2 + 2x + 1 - 1)
We can see the +1 and -1 term now cancel out leaving us with:
2(x^2 + 2x)
And finally we take the common term from within the bracket to the outside (both terms share an x) to finish with:
2x(x + 2)

Answered by Django M. Maths tutor

2405 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

(a) The equation of a line L is 2x-3y=6. Find the gradient of L. (b) Find the equation of the line which is parallel to L and passes through the point (6,9)


Solve for x, y, and z: 5x - 2y = 19 , 3x + 3z = 21 , y + z = 2


Write y = x^2 + 4x + 6 in the form y = (x + a)^2 + b. What is the minimum value of y?


Consider f:R -> R, f = x/ sqrt(x^2+1). Prove that for any a between -1 and 1, f(x)=a has only one solution.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences